2022
DOI: 10.1007/s12552-022-09357-4
|View full text |Cite
|
Sign up to set email alerts
|

Values and Attitudes Toward Immigrants Among School Children in Switzerland and Poland

Abstract: Research on key determinants of negative attitudes toward immigration has often suggested that values held by individuals systematically explain such sentiments. Universalists appear to have more positive and conservatives more negative attitudes. So far, however, these insights are based on studies using adult samples. In our study, we analyze these relations among children and adolescents. For the analysis, we utilized a Swiss-Polish panel dataset (2015–2017, N = 5,332) with three time points collected among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Violante et al (2020) concluded in a study with American preschoolers that children consider Englishspeaking individuals who were born and raised in the USA as Americans rather than individuals who immigrated to their country. Becker et al (2022) concluded in a study with children living in Switzerland and Poland that children demonstrated negative attitudes and behaviours towards immigrants living in their countries and this circumstance did not have any difference from the attitudes of their parents. Demintseva (2020) stated in her study with children in Russia that there are children of different ethnic origins in these schools, where certain schools are perceived as immigrant schools.…”
Section: Discussionmentioning
confidence: 94%
“…Violante et al (2020) concluded in a study with American preschoolers that children consider Englishspeaking individuals who were born and raised in the USA as Americans rather than individuals who immigrated to their country. Becker et al (2022) concluded in a study with children living in Switzerland and Poland that children demonstrated negative attitudes and behaviours towards immigrants living in their countries and this circumstance did not have any difference from the attitudes of their parents. Demintseva (2020) stated in her study with children in Russia that there are children of different ethnic origins in these schools, where certain schools are perceived as immigrant schools.…”
Section: Discussionmentioning
confidence: 94%
“…Schwartz (Schwartz 1994, p. 21; see also Schwartz et al 2012) defines basic human values as ‘transsituational goals, varying in importance, that serve as guiding principles in the life of a person or other social entity’. Basic human values have been used to explain a plethora of attitudes such as those towards immigrants (Becker et al 2022; Davidov and Meuleman 2012), pro‐environmental policies (referenced de Groot and Thøgersen 2018), European integration (Dennison et al 2020, 2021) or as forming and giving content to political ideology (Piurko et al 2011), just to name a few. Following from that, basic human values are likely to play a role in the formation of preferences towards a social benefit scheme in Europe, too.…”
Section: Schwartz's Basic Human Valuesmentioning
confidence: 99%
“…It could be argued that also identities and identification are formed in early age. At the same time, previous studies have shown that universalism is formed and activated as early as in early school age (e.g.,Becker et al 2022) whereas European identity is still in formation. Whether and to what extent values are formed earlier than more complex identities such as identification with Europe may be a topic for future research.…”
mentioning
confidence: 99%